2013
DOI: 10.1111/php.12107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentration on the Photophysics of Dyes in Light‐Scattering Materials.

Abstract: Photoactive materials based on dye molecules incorporated into thin films or bulk solids are useful for applications as photosensitization, photocatalysis, solar cell sensitization and fluorescent labeling, among others. In most cases, high concentrations of dyes are desirable to maximize light absorption. Under these circumstances, the proximity of dye molecules leads to the formation of aggregates and statistical traps, which dissipate the excitation energy and lower the population of excited states. The sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 81 publications
(88 reference statements)
2
31
0
Order By: Relevance
“…Even at concentrations for which reabsorption is negligible, red shifts still persist on increasing dye concentration. Concentration‐dependent Stokes shifts, found generally in dyed materials at high concentrations, are attributed to long‐range interactions (at distances higher than 10 nm) between excited dye molecules and neighboring molecules in the ground state . At the highest concentrations, spectra are still affected by reabsorption, though to a lesser extent than for thick layers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Even at concentrations for which reabsorption is negligible, red shifts still persist on increasing dye concentration. Concentration‐dependent Stokes shifts, found generally in dyed materials at high concentrations, are attributed to long‐range interactions (at distances higher than 10 nm) between excited dye molecules and neighboring molecules in the ground state . At the highest concentrations, spectra are still affected by reabsorption, though to a lesser extent than for thick layers.…”
Section: Resultsmentioning
confidence: 98%
“…2 correspond to twice the standard deviation in the excitation interval 500-540 nm for EoY and 535-555 nm for PhB. The remaining decrease has to be attributed to mechanisms other than reabsorption and reemission, namely static quenching due to the absorption of aggregates or virtual traps and to dynamic quenching produced by excitation energy migration to those entities (29).…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation behavior is also strongly affected by external (dye environment related) factors such as temperature, pH, concentration of the dye, ionic strength, and solvent polarity. One of the main consequences of the self‐assembly of dyes is that molecular aggregates have distinct photophysical properties compared to the individual monomer . In many cases the strong intermolecular interactions that hold aggregates together are responsible for the weakening of emission (“aggregation‐caused quenching”) and this may severely limit the use of the dyes in real‐world applications such as organic light‐emitting diodes (OLEDs) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the near monolayer coatings of dye found on the 100 nm nanoshells as well as their separation by an 8 nm silica shell results in a lower localized dye concentration, which has been shown to reduce the formation of energy traps (aggregates of dye molecules that decay absorbed energy non-radiatively) and thus limit self-quenching. [74,75] Previous studies with higher ICG dye loading than the present nanoshells and microshells have shown a that increasing localized ICG concentration on shells results in severe selfquenching.…”
Section: Elemental Analysis Of Shell Wallmentioning
confidence: 72%